Investigation of the specific toxicity of a non-steroidal anti-inflammatory veterinary drug based on celecoxib - M. L. Kondratyuk (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
Laboratory studies were conducted to determine the subacute toxicity of the veterinary drug Celexib on white rats and dogs. The drug “Celexib,” based on celecoxib, is used in sports horses, dogs, fallow deer, red deer, wild pigs, and cats for the treatment of acute and chronic diseases of the musculoskeletal system (arthritis, myositis, laminitis, etc.), pain syndrome (post-operative and post-traumatic), symptomatic therapy for diseases accompanied by animal fever. When administered subcutaneously to rats, the drug “Celexib” (solution for injections) under the conditions of a subacute toxicological experiment in doses of 0.1–1.0 ml/kg does not cause hemo-, hepato- and nephrotoxic effects on the body of laboratory animals. However, 3-day administration of the drug, in the indicated doses, led to a probable (Р < 0.05) decrease in the number of leukocytes by 14.6, 13.1, and 13.4 %, respectively. After 7 days, after stopping the administration of the drug, a tendency to decrease these indicators was observed. The exception was the tendency to increase the activity of the hepatospecific enzymes ALT and AST one and 3 days after the start of the administration of the drug, at a dose of 1.0 ml/kg of body weight, which 7 days after the cessation of subcutaneous administration of the drug, did not differ from those in the control group. When administered subcutaneously to dogs, the drug “Celexib” (solution for injections) under the conditions of a subacute toxicological experiment in doses of 0.1–1.0 ml/kg does not cause hemo-, hepato- and nephrotoxic effects on the body of laboratory animals, although a 3-day administration of the drug in the indicated doses led to a probable (Р < 0.05) decrease in the number of leukocytes by 20.3; 19.5 and 19.8 %, respectively, which began to decrease 7 days after stopping the administration of the drug. The exception was the tendency to increase the activity of the hepatospecific enzymes ALT and AST and the concentration of urea one and 3 days after the start of administration of the drug at a dose of 1.0 ml/kg of body weight, which did not differ from those after 7 days after the cessation of subcutaneous administration of the drug in the control group. Further studies will be the next stage of pre-registration tests aimed at studying the embryotoxic and carcinogenic effect of “Celexib,” which is mandatory material of the “Safety and residue studies” section of the dossier for this medicinal product.